Development and Validation of a Theory of Planned Behavior Based Instrument for Measuring Stunting Prevention Behavior Among Mothers of Children Under Five in Indonesia - Nur, A Fahira; Mujianti, Cicik; Sofyana, Sherllia; Arifuddin, Adhar (Journal of Health and Nutrition Research, 2025)
Stunting remains a critical public health issue in Indonesia, with a national prevalence of 19.8% in 2024 and 24.7% in urban areas, such as Palu City. Maternal behaviors play a pivotal role in prevention, yet no validated instrument has measured stunting prevention behaviors based on behavioral theory. To develop and validate a Theory of Planned Behavior (TPB) based instrument to assess stunting prevention behaviors among mothers of children under five in Indonesia. An instrument development and validation study was conducted in Palu City, Sulawesi Tengah, from May to December 2025. The study followed five phases: (1) literature review and blueprint construction (50 items), (2) content validation by five experts using Aiken’s V, (3) pilot testing with 30 mothers, (4) large-scale data collection from 300 purposively selected mothers, and (5) psychometric validation using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Data analysis was performed with R software. Expert review confirmed 45 items (90%) valid (Aiken’s V ≥ 0.80). Pilot testing showed high reliability (Cronbach’s α = 0.922). EFA and CFA supported a five-factor structure consistent with TPB, with good model fit (CFI = 0.974, TLI = 0.973, RMSEA = 0.019, SRMR = 0.075). Internal consistency was strong (Cronbach’s α = 0.884). The TPB-Stunting Instrument is a reliable, valid, and culturally relevant tool for measuring maternal behaviors in stunting prevention programs.